Egypt's desert paradoxes, promises, and possibilities: A study of land reclamation policies along Cairo-Alexandria desert road - Salman, Salwa Yehia (AUC Knowledge Fountain, 2018)
In 2016 ‘People’s Right’ campaign, also known as the National Committee for Retrieving Looted State Lands, was assigned to either retrieve or facilitate the formal registration of state lands according to occupants’ personal cases. This study explores the official representations of desert land reclamation, allocation, and distribution, with a focus on the (re-) conceptualization of rights, state territoriality, and sovereignty as a part of an emerging national narrative on state lands and property rights. The study draws on methodological insights in the anthropology of development which employs a Foucauldian discourse analysis to examine ‘development’ and the role of the state under neoliberalism. Through the lens of an unregistered settlement, Ard Baza, the study puts national narratives of desert development and property rights in conversation with individual cases to explore both property and state/society relations. In this framework, I examine several sources including state publications, presidential speeches, newspapers’ archives, and official publications between 1952 and 2011. I also explore the history of Ard Baza between 1989 and 2016 through semi-structured interviews with occupants, a sample of land contracts, and other legal documents.